Antiamoebic Chemoprophylaxis Using Quinfamide in Children: A Comparative Study. (2002) - Padilla, Nicolas; Diaz, Rosalinda; Alarcon, Alfonso; Barreda, Roberto
Abstract : This study sought to examine whether the administration of quinfamide at 3- or 6-month intervals diminished the frequency of Entamoeba histolytica cysts in stool samples compared to controls. The prospective, longitudinal, randomized, single-blind study examined children from six primary schools in Celaya and Neutla, Guanajuato. Of the 1, 524 students in these schools, we selected participants for the study as follows: Children were included in the study if their parents agreed in writing to the study and if the children demonstrated evidence of E. histolytica cysts after a parasitoscopic analysis by concentration (PSC) in three samples over consecutive days using Faust's method. Those included in the study received a single 4.3-g/kg dose of quinfamide, and we performed PSC on days 5, 6, and 7 following dose administration to examine whether quinfamide had affected the presence of the cysts. The study participants who tested negative for cysts were divided into three groups: Group 1 had 102 patients who underwent quinfamide treatment and three CPS analyses after the 12 months of the study; Group 2 had 98 subjects who underwent the quinfamide treatment and three CPS analyses at months 3, 6, 9, and 12 after their entrance into the study; and Group 3 had 102 patients, who underwent the quinfamide treatment and series of three CPS analyses at months 6 and 12 of the study. All participants received the dose of quinfamide after providing stool samples and after a clinical gastrointestinal history was obtained. Further clinical gastrointestinal data were collected 5 days after the quintamide dose was administered. We used EpiInfo 6.0 for statistical analysis, calculating X 2 and p values for the clinical data and the CPS data after the 12 months concluded. Of the initial samples of 1, 524 subjects, 308 (20.2%) had Entamoebic cysts. Of these, six were further eliminated because they did not meet the inclusion requirements. At the conclusion of the study, Group 1 presented with 37.6% of subjects still testing positive for cysts; of Group 2, 12.5% tested positive; and in Group 3, 23.5% of participants tested positive for cysts ( X 2 = 16.8; df = 2; p = 0.0002). For comparisons of groups 1 and 2 and 1 and 3, p > 0.05. We conclude that antiamoebic chemoprophylaxis can be a choice for control of amoebic infection where personal hygiene and food consumption habits are not improving.